Taguchi based parameter optimization for cutting force reduction in SAE 1045 steel machining with nanofluid. (2022) - Malladi, Avinash; Saravanan, R.; Gnanavel, C.; Rajesh, S.; Sekar, C.B.; Nagarathi, D.K.
Highlights: A shift manufacturing method from CNC to Conventional machining with use of Nano fluid is focused. Compared and statistically tested the outcome of Cutting force encountered in green machining and Nanofluid based wet machining. Taguchi Experimental design and Analysis employed in this investigation. The average reduction of 12.46% cutting force with nanofluid was recorded. Abstract: Utilization of Kerala chips shop's waste of 'used coconut oil' is considered its natural lubricating properties. This piece of research investigating the effects of Nano Acidum Boricum powder enriched waste coconut oil on diminishing cutting forces while machining SAE1045 steel. The performance of nanofluid effects on machining is compared with its conventional practice of green machining. As waste is utilized to prepare bio degradable nanofluid for employing for better machinability. This process named as clean machining. The machining outcomes on SAE1045 steel work were compared with t -test. This investigation considered depth of cut, cutting speed and tool feed rate at three levels Taguchi L27 orthogonal array was utilized.. Taguchi analysis considered for optimizing the machining parameters with the sense of surface roughness. The ANOVA utilized to analyses the observations, influence of various input factors and their levels. It was found that the proposed method reduces the surface roughness considerably. By altering the cutting speed, the required cutting force could be met than the tool feed rate.